Adult-Onset Still’s Disease-like Syndrome following COVID-19 Vaccination: A Case Report and Review of the Literature - Poramed Winichakoon; Wanitcha Chanloung; Teerapat Nantsupawat; Worawit Louthrenoo (Vaccines, 2022)
Adult-onset Still’s disease (AOSD)-like syndrome has rarely been reported as a complication of COVID-19 vaccination. This study reports a 31-year-old female patient who presented with fever, myalgia, arthralgia, pleuropericarditis, leukocytosis, and transaminitis following ChAdOx1 vaccination, and met Yamaguchi’s criteria. A PubMed literature search, performed up until March 2022, identified 10 such cases. A total of 11 cases, including the one in this report, developed AOSD-like syndrome after administration of the viral vector (ChAdOx1) vaccine (six patients) and mRNA vaccine (five patients: BNT162b2 in four and mRNA-1273 in one). There were four male and seven female patients, with their median (Q1, Q3) age and the onset of symptoms after vaccination being 36 years (29, 45) and 10 days (6, 13), respectively. Fever (100%), arthralgia/arthritis (90.9%), skin rashes (81.8%), and sore throat (81.8%) were the main clinical findings. Pericarditis (45.5%), myocarditis/cardiac dysfunction (36.4%), pleuritis (54.6%), and pulmonary infiltrations (36.4%) were also common. One patient developed macrophage activation syndrome. One patient responded well to non-steroidal anti-inflammatory drugs, and the other six showed a good response to high-dose corticosteroids alone. Of the remaining four patients, who showed partial responses to high dose corticosteroids, showed good responses to biological agents. AOSD-like syndrome following COVID-19 vaccination shared many similar clinical features and treatment outcomes to those of idiopathic AOSD (but with a higher prevalence of cardiopulmonary involvement in the former). Physicians should be aware of this extremely rare complication to achieve early diagnosis and provide proper management.